Pemanfaatan Limbah Abu Terbang (Fly Ash) Batu Bara Sebagai Bahan Campuran Beton Geopolimer - Julharmito Julharmito; Ahmad Fadli; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Fly ash can be used in the manufacture of concrete geopolimer. The replacement of the use of cement with fly ash can reduce the cost of manufacture of concrete and can reduce global warming posed from the production of cement. This research aims to know the influence of the use of fly ash, variations in concentrations of KOH and Na2SiO3/KOH ratio relationships against the concrete compressive strength of concrete geopolimer and test the level of immobilisasi of heavy metals contained in concrete geopolimer. Geopolimer synthesized from fly ash using a mixed solution of KOH and Na2SiO3. The solution is prepared the day before use. Initially prepared a solution of KOH with concentrations of 8 M, 10 M, 12 M, 15 M and Na2SiO3/KOH ratio 0.8; 1.2; 1.6; 2.0. These materials are mixed while stirring and inserted into the mold cylinder diameter 4 cm height 8 cm. Batter the already hardened issued and in the dry at a temperature of 80оC for 24 hours, then the samples were dried at room temperature for 21 days, then performed a test of strong press, porosity and heavy metal content. Test result showed a strong increase with added press Molarity KOH and Na2SiO3/KOH ratio, strongly press the highest 30.26 MPa produced on the molar ratio of 14 m and Na2SiO3 KOH/KOH 2.0. Instead, the porosity obtained decreased with increasing molar NaOH and KOH Na2SiO3/ratio. The lowest porosity 6.49% obtained in Molarity KOH 14 and Na2SiO3/KOH ratio is 2.0. Concrete geopolimer able to immobilize heavy metals found in the fly ash with either. Metal Pb reduced from 8,954 mg/L be 0.66 mg/L, the metal Cr reduced from 6,978 mg/L be 2.096 mg/L, Cu Metal reduced from 12.355 mg/L be 7.350 mg/l. so as to meet the Government Regulation Number 101 by 2014.Key word: geopolimer concrete, fly ash, activator solution